Automatic Verification of Real-Timed Systems Using EPSILON - Godskesen, Jens Chr.; Larsen, Kim G.; Skou, Arne (BRICS Report Series, 1994)
In this paper we report on an application and extension of the theory of Timed Modal Specifications (TMS) and its associated verification tool EPSILON. The novel feature with which EPSILON has been extended is the ability to automatically generate diagnostic information in cases of erroneous refinement steps.